A study of carotenoids of mango fruit and mango based if products and their in-vitro bioavailability - Wansapala, M.A.J. (My University, 2016)
Attached

Vitamin A is an important micronutrient of animal origin responsible for structure and functioning of the skin, mucous membrane and maintaining of a good vision. Low-income, poor educational background and cultural and religious practices discourage the intake of recommended amount of vitamin A through animal sources. Therefore the attention should be given to the naturally available and affordable provitamin A sources such as green leafy vegetables, certain root crops and most of the fruits. The major objectives of this study were to qualitatively analyze the carotenoid profile in three popular mango varieties namely "Karuthacolamban”, "Beti Amba" and "Gira Amba" grown in the three different agro climatic regions of the Sri Lanka, quantification and in vitro bioavailability of pro vitamin A content in all three varieties with a view to updating the database. The impact of different process conditions on the stability of provitamin A carotenoids in mango based products (ie. jam, cordial and osmotically dehydrated mango) were also studied. Sensory characteristics of the selected mango varieties were comparatively studied and the sensory web was developed for each variety. A reversed phase HPLC method has been developed for the study for the separation and extraction of the carotenoids in crude and saponified extracts from the Karuthacolamhan", "Beti Amba" and “Gira Amba" and mango based products. All fruits with the same maturity indices were selected from local market and the cultivars were identified by Horticultural Crop Research and Development Institute Gannoruwa. Kandy, Sri Lanka. Carotenoids from mango were extracted according to the method described by Rodriguez Amaya (1999), which involved extraction of carotenoids partition to petroleum ether separation of carotenoids by Open Column Chromatography (OCC) identification of carotenoids using Ultra violet Visible absorption spectra (maximum absorption and spectral fine structure), order of elution in 0CC and chemical tests. Purity of the identified carotenoids were further confirmed by using the High Performance Liquid Chromatography with photo diode array detection (C18 column Spherisorb ODS2. 5im, 4.6mm x 1 50mm; gradient elution of mobile phase of Methanol, Acetonitrile and 0.05% Tri ethyl amine in Ethyl acetate). The HPLC analysis of crude extract of variety Karuthacolamban highlighted the existence of four main peaks which had UV- Visible spectra similar to those reported for violaxanthin, neoxanthin, n-carotene and u-cryptoxanthin. The HPLC analysis of crude extract of "Beti Amba" and Gira Amba" varieties highlighted the existence of three main peaks which had UV- Visible spectra similar to those reported for violaxanthin, neoxanthin. and 3-carotene .A saponification step of crude extracts indicated the existence of esterified violaxanthin, neoxanthin, and a-cryptoxanthin. The Variety "Karuthacolomban" contains 2.7±0.3 ig/g (Fresh weight) the variety "Beti Amba" contains 2.6±0.3 tg/ g (Fresh weight) and the variety "Gira Amba" (0.1 8 + 0.6 pg/ g (Fresh weight) of l- carotene as the principal pro-vitamin A carotenoid .The amount of in vitro bioavailability 3- carotene was highest in the Beti Amba" variety (29.6%) than "Karuthacolomban" (24%) and "Gira Amba" (20.30%). Thus, this study has indicated that varietal difference does not exist in the content but bioavailability of 3-carotene in mango. The percentages of destruction of - carotene in jam, cordial and osmotically dehydrated mango during the process were recorded as 89%, 78% and 66% respectively. The in vitro bioaccessibility of 3- carotene in all three products were recorded as 67 %, 25 % and 64% respectively. 1-ligher amounts of provitamin A carotenoids (1.43±0.3 jig! g Fresh weight) were obtained under Room temperature (28 °C) and the lowest amount of provitamin A carotenoids (0.20±0.3 jig! g Fresh weight) were recorded at -2 T. The provitamin A carotenoids content of artificially ripened mango was (0.30±0.3 jig/ g Fresh weight) lower than that of the natural. The highest sensory values were recorded 'Gira amba" variety.